2023
DOI: 10.1101/2023.01.19.524823
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immune sensing of food allergens promotes aversive behaviour

Abstract: In addition to its canonical function in protecting from pathogens, the immune system can also promote behavioural alterations. The scope and mechanisms of behavioural modifications by the immune system are not yet well understood. Using a mouse food allergy model, here we show that allergic sensitization drives antigen-specific behavioural aversion. Allergen ingestion activates brain areas involved in the response to aversive stimuli, including the nucleus of tractus solitarius, parabrachial nucleus, and cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…An interesting example for food preference decisions beyond taste and hedonic value is immune sensing of food allergens (Florsheim et al, 2023). Studies have shown that humans suffering from food allergies—sometimes mismatched with “picky eaters”—learn to make food preference or aversion decisions to avoid the intake of allergens being harmful to their health (Plum et al, 2023; Rothenberg, 2023).…”
Section: Food Preference Enigmasmentioning
confidence: 99%
“…An interesting example for food preference decisions beyond taste and hedonic value is immune sensing of food allergens (Florsheim et al, 2023). Studies have shown that humans suffering from food allergies—sometimes mismatched with “picky eaters”—learn to make food preference or aversion decisions to avoid the intake of allergens being harmful to their health (Plum et al, 2023; Rothenberg, 2023).…”
Section: Food Preference Enigmasmentioning
confidence: 99%
“…Mice were immunized with ovalbumin (OVA) egg white protein in alum gel that evokes high concentrations of anti-OVA IgE antibody. 12,13 After drinking OVA water, OVA-allergic but not controlled mice developed allergic inflammation in the stomach and small intestines with diarrhea. OVA-allergic and control mice were then offered drinking water without and with OVA.…”
Section: Leukotriene Mediation Of Avoidance Behaviormentioning
confidence: 99%
“…Challenge of sensitized mice once with OVA resulted in neuronal activation that was detected biochemically in brain tissue from the nucleus tractus solitarius, external lateral parabrachial nucleus, and central amygdala. 12 However, no decrease in antigen avoidance was observed after disruption of input from the vagus nerve or dorsal root sensory neurons that transmit signals from internal organs, including the gastrointestinal tract, through the nucleus tractus solitarius to the parabrachial nucleus (PBN). Levels of growth and differentiation factor 15 (GDF15) were increased significantly in gastrointestinal epithelial cells of antigen-avoiding mice through a mast cell-and IgE-dependent pathway.…”
Section: Leukotriene Mediation Of Avoidance Behaviormentioning
confidence: 99%
See 2 more Smart Citations